Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1161/01.atv.0000153516.02782.65
|View full text |Cite
|
Sign up to set email alerts
|

IL-18 Accelerates Atherosclerosis Accompanied by Elevation of IFN-γ and CXCL16 Expression Independently of T Cells

Abstract: Objective-The proatherogenic effect of IL-18 is shown to be dependent on IFN-␥ production. It is believed that activated T cells play a proatherogenic role through secretion of IFN-␥. However, recent studies in vitro have shown that macrophages, NK cells, and even vascular smooth muscle cells may also secrete IFN-␥ after stimulation by cytokines like IL-18. We therefore investigated whether cells other than activated T cells can play a proatherogenic role via IFN-␥ secretion under the stimulation of IL-18 in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
1
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(79 citation statements)
references
References 56 publications
2
69
1
6
Order By: Relevance
“…27 In this issue, an elegant study by Tenger et al demonstrates that the proatherogenic role of IL-18 goes beyond its effect on the Th1 polarization, because IL-18 -mediated acceleration of atherosclerosis is detected in apoE Ϫ/Ϫ /SCID mice in the absence of T cells. 1 The authors show that IL-18 -induced IFN-␥ production in macrophages and NK cells is accompanied by an upregulation of the CXCL16 scavenger receptor in lesions. This cascade of events is likely to be responsible for increased foam cell formation and fatty streak development under IL-18 treatment.…”
Section: See Page 791mentioning
confidence: 99%
“…27 In this issue, an elegant study by Tenger et al demonstrates that the proatherogenic role of IL-18 goes beyond its effect on the Th1 polarization, because IL-18 -mediated acceleration of atherosclerosis is detected in apoE Ϫ/Ϫ /SCID mice in the absence of T cells. 1 The authors show that IL-18 -induced IFN-␥ production in macrophages and NK cells is accompanied by an upregulation of the CXCL16 scavenger receptor in lesions. This cascade of events is likely to be responsible for increased foam cell formation and fatty streak development under IL-18 treatment.…”
Section: See Page 791mentioning
confidence: 99%
“…In ApoE / mice treated only with IL-18, which is known to be an inducer of INF , a similar effect occurred as when they were subjected to direct INF treatment. In this way, it was demonstrated that CXCL16 mRNA expression could be also indirectly triggered 30) . All these findings reflect the complexity of the CXCL16 regulation pathway, which could be modified on different levels of the CXCL16 gene regulatory network.…”
Section: -1 Cxcl16: Unique Chemokine On Separate Gene Locusmentioning
confidence: 88%
“…[36] It plays a critical role in atherosclerosis in ESRD patients. [37][38][39] Mallat et al had found that IL-18 binding protein can reduce atherosclerosis. [40] In our study, the plasma IL-18 level was reduced after six months of HDF, which may result in less IL-18 related atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%